Dietary supplementation of ginger and turmeric improves reproductive function in hypertensive male rats. (2015) - Akinyemi, Ayodele Jacob; Adedara, Isaac A.; Thome, Gustavo Roberto; Morsch, Vera Maria; Rovani, Monique Tomazele; Mujica, Lady Katerine Serrano; Duarte, Thiago; Duarte, Marta; Oboh, Ganiyu; Schetinger, Maria Rosa Chitolina
Abstract: Ginger [ Zingiber officinale Roscoe (Zingiberaceae)] and turmeric [ Curcuma longa Linn (Zingiberaceae)] rhizomes have been reportedly used in folk medicine for the treatment of hypertension. However, the prevention of its complication such as male infertility remains unexplored. Hence, the aim of the present study was to investigate the preventive effects of ginger and turmeric rhizomes on some biomarkers of male reproductive function in L-NAME-induced hypertensive rats. Male Wistar rats were divided into seven groups ( n  = 10): normotensive control rats; induced (L-NAME hypertensive) rats; hypertensive rats treated with atenolol (10 mg/kg/day); normotensive and hypertensive rats treated with 4% supplementation of turmeric or ginger, respectively. After 14 days of pre-treatment, the animals were induced with hypertension by oral administration of L-NAME (40 mg/kg/day). The results revealed significant decrease in serum total testosterone and epididymal sperm progressive motility without affecting sperm viability in hypertensive rats. Moreover, increased oxidative stress in the testes and epididymides of hypertensive rats was evidenced by significant decrease in total and non-protein thiol levels, glutathione S -transferase (GST) activity with concomitant increase in 2′, 7′-dichlorofluorescein (DFCH) oxidation and thiobarbituric acid reactive substances (TBARS) production. Similarly, decreased testicular and epididymal NO level with concomitant elevation in arginase activity was observed in hypertensive rats. However, dietary supplementation with turmeric or ginger efficiently prevented these alterations in biomarkers of reproductive function in hypertensive rats. The inhibition of arginase activity and increase in NO and testosterone levels by both rhizomes could suggest possible mechanism of action for the prevention of male infertility in hypertension. Therefore, both rhizomes could be harnessed as functional foods to prevent hypertension-mediated male reproductive dysfunction.